Seleção de pessoal: a visão dos gestores - Niemeyer, Luciana Grasseschi Mathias Duarte (2012)
This paper aims to discuss the vision of managers regarding the selection of staff today and evaluate the potential for using the Systemic Organizational Placement in the selection processes. Throughout the work presented the story of the evolution of the selection process, both from the management science point of view and the psychology point of view, the contemporary model of personnel selection Systemic Organizational Placement as a selection tool. This study is based on an applied research with an exploratory and descriptive character with a qualitative approach. The survey research procedure is used seeking to measure the opinion of a distinct population of respondents